The Effect of Instruction Using Arithmetic Bowling and Snake and Ladder Games In Increasing Cognitive Development of Early Childhood In Ambon City - Hermalina Abarua; Lamberthus J. Lokollo (International Journal of Education, Information Technology, and Others, 2021)
Abstract: This study aims to 1) determine the effect of arithmetic bowling on cognitive development in early childhood education institutions in Ambon city, 2) determine the effect of the snakes and ladders game on cognitive development in early childhood education institutions in Ambon city, 3) determine the effect of differences in learning in early childhood education by using arithmetic bowling, snake and ladder game in improving cognitive development of children in early childhood education institutions in Ambon city. This study used a quasi-experimental method, with an ex-post-facto approach. The population of this study were all students of Mawar early childhood education Faculty of Education Pattimura University Ambon. 20 respondents were taken by using the proportional random sampling technique which randomly carried out 2 classes. The data were collected through the observation instrument of the cognitive abilities of mathematical concepts. The results of this study indicated that 1) children in the experimental group Mawar early childhood education had a cognitive ability of mathematical concepts using bowling arithmetic game. They showed very good activity with the lowest score of 28 and the highest score of 40, the average value is 35.4 with a median of 35.5 and mode. 35, 2) Children in the control group have cognitive abilities in mathematical concepts using snake and ladder game, showing well-developed activities with the lowest score of 24 and the highest score of 38, the average value is 30.4 with a median of 30.5 and a mode of 31, 3) There was a difference in the average cognitive ability of mathematical concepts of children aged 5-6 years between students taught using bowling arithmetic and students taught using snake and ladder games with a count value = 2.78 while ttable with n1 + n2 degrees of freedom -2 = 18 at the significance level α = 0.05 can be 30 1.73 then tcount> ttable, this means the difference both means are significant at the 0.05 level. It can be concluded that there is a difference in the average cognitive ability of early childhood science concepts in the experimental group and the control group. Thus, it can be concluded that there was an effect of experimental methods and demonstration methods on the cognitive ability of children aged 5-6 years in early childhood education of Ambon City.